2010
DOI: 10.1080/00379271.2010.10697673
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Andean-Ecuadorian populations ofAnastrepha fraterculus(Wiedemann 1830) (Diptera: Tephritidae) inferred from COI and COII gene sequences

Abstract: Abstract. Phylogenetic relationships among Andean-Ecuadorian and other Neotropical populations ofAnastrepha fraterculus and related species have been studied using two regions of mtDNA : 405 base pairs within Cytochrome Oxidase I ( COI) and 224 base pairs within Cytochrome Oxidase II (COII). Phylogenetic relationships were inferred using Maximun Parsimony (MP) method and haplotype networks. Andean-Ecuadorian populations of A. fraterculus are monomorphic at the COI locus and fall within a clade of South-America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In the phylogenetic analysis, all C. capitata bred from M. zeyheri were grouped together in a single clade, with the isolates obtained from the NCBI database showing a monophyletic relationship. The isolates were also rich in AT nucleotidic composition, which is consistent with previous descriptions for other insects 23 and mites. 24 This is the first confirmed report of C. capitata on M. zeyheri.…”
Section: Discussionsupporting
confidence: 87%
“…In the phylogenetic analysis, all C. capitata bred from M. zeyheri were grouped together in a single clade, with the isolates obtained from the NCBI database showing a monophyletic relationship. The isolates were also rich in AT nucleotidic composition, which is consistent with previous descriptions for other insects 23 and mites. 24 This is the first confirmed report of C. capitata on M. zeyheri.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Ludueña et al (2010) reported a distinct clade in the Ecuatorian Andes, whereas Ruiz-Arce et al (2012) revealed the existence of six genetically distinct populations of A. obliqua among which the magnitude of differences warrants taxonomic revision. However, the A. fraterculus group as a whole may still contain substantial hidden diversity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the A. fraterculus group as a whole may still contain substantial hidden diversity. For example, Ludueña et al (2010) reported a distinct clade in the Ecuatorian Andes, whereas Ruiz-Arce et al (2012) revealed the existence of six genetically distinct populations of A. obliqua among which the magnitude of differences warrants taxonomic revision. This recent and rapid differentiation renders the A. fraterculus species group a potential model for the understanding of divergence in tropical frugivorous insects but also renders management of pest species a highly complex task.…”
Section: Smithmentioning
confidence: 99%
“…Microsatellites were developed (Lanzavecchia et al 2014) and proved to be successful to discriminate among morphotypes (Lima et al unpublished data, Manni et al 2015). The phylogenetic relationships of Andean-Ecuadorian populations were determined with other molecular markers (Ludeña et al 2011). …”
Section: Situation Analysis At the Start Of The Crp And Ouputs For Eamentioning
confidence: 99%